2016
DOI: 10.5713/ajas.16.0588
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on production, reproduction and functional traits between Fleckvieh and Braunvieh cattle

Abstract: ObjectiveAim of the current comparative study was to evaluate production outputs, reproduction efficiency and functional traits in dual-purpose Fleckvieh and Braunvieh cows, reared under temperate European conditions.MethodsA data-set from 414 Fleckvieh and 42 Braunvieh cows and 799 lactations was analysed. ID tag number, milk yield per milking session, number of steps/interval and milk conductivity were recorded and collected daily using AfiMilk 3.076 A-DU software (Afimilk Ltd., Kibbutz, Israel). Production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
5
13
0
Order By: Relevance
“…Overall our finding are in accordance with finding reported by Cziszter et al (2017), their reported lower values of analysis of reproduction traits in Simmental cattle reared in Romania (32.8 ± 0.29 months for AFC, 122.0 ± 4.11 days for DO, 1.78 ± 0.03 times for NIC and 385.8 ± 1.65 days for CI). These results are similar with our findings.…”
Section: Analysis Of Reproduction Traits For the Whole Periodsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall our finding are in accordance with finding reported by Cziszter et al (2017), their reported lower values of analysis of reproduction traits in Simmental cattle reared in Romania (32.8 ± 0.29 months for AFC, 122.0 ± 4.11 days for DO, 1.78 ± 0.03 times for NIC and 385.8 ± 1.65 days for CI). These results are similar with our findings.…”
Section: Analysis Of Reproduction Traits For the Whole Periodsupporting
confidence: 93%
“…The reproduction traits in population dairy cows of the Simmental cattle were evaluated by Ulutaş and Sezer (2009), Pantelić et al (2011), Bujko et al (2013), Cziszter et al (2017), Toledo-Alvarado et al, (2017, Bujko et al (2018a) and others.…”
Section: Introductionmentioning
confidence: 99%
“…The content components of milk in kg had an increasing tendency, which was directly related to the increase in milk production, where a high positive correlation dependence as stated Bujko, 2011;Cziszter et al, 2017;Bujko et al, 2018a;Karamfilov and Nikolov, 2019. The decrease in the average value of fat content for the evaluated period is also due to the optimization of the feed ration, which is related to the reduction of fibre content and thus the increase of easily digestible carbohydrates.…”
Section: Figurementioning
confidence: 80%
“…in Slovakia (Strapák et al, 2013;Kadlečík et al, 2017;Bujko et al 2018aBujko et al ,b, 2019Kasarda et al, 2019), Austria (Ledinek et al, 2019), Serbia (Perišić et al, 2009, Bulgaria (Karamfilov and Nikolov, 2019), Turkish (Bolacali and Öztürk, 2017;Öner et al, 2019), Romanian (Grădinaru et al, 2014;Cziszter et al, 2017), Poland (Zółkiewski et al, 2018, France (Doublet et al, 2019), Mexican (Utrera et al, 2018) and other countries (Strapák et al, 2013).…”
Section: Changes In Production and Reproduction Traits In Population mentioning
confidence: 99%
See 1 more Smart Citation